Thyroid hormones, blood glucose and glycosylated hemoglobin in healthy Sudanese subjects - Eisa, Abdelmuhsin H.; Bashir, Amir A.; Osman, Asim A.; Ali, Ibrahim A.; Awad, Kamal M.; Hajo, Elnagi Y.; Taha, Elmutaz H.; Alborai, Abeadalla A.; Musa, Omer A. (International Journal of Advances in Medicine, 2019)
Background: Diabetes mellitus and thyroid diseases are the most prevalent metabolic disorders in Sudan. The value of HbA1C reflects the glycemic status over the last 2-3 months. So, in this study, an insight for thyroid hormone regulation of glucose metabolism is investigated. Is to study the association between thyroid hormones levels, fasting blood sugar (FBS) and HbA1c in healthy adults. Methods: A cross sectional study was performed in a healthy Sudanese cohort in the period between September 2017 to November 2018, involving 610 healthy adult Sudanese aged 20 to 60 years. HbA1c, fasting blood sugar (FBS), T3, T4 and TSH were measured. Results: The study results demonstrated a significant association between the median concentration of T3 and T4 with plasma level of HbA1c. A significant linear correlation between serum concentration of T3 and fasting blood sugar (FBS) was observed. Inverse correlation was detected between serum TSH and HbA1c, FBS in study population. Conclusions: The present study concluded that FBS and HbA1c levels were increased with increasing of both T3 and T4. Based on this study all the thyroid patients’ especially hyperthyroid patients should have regular checkup of their glucose levels.